Kewajiban dalam Pemikiran Immanuel Kant dan Relevansinya dengan Akhlak Islam - Effendi, Rahmat (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Many thinkers discuss ethics as something inherent in life, one of which is Immanuel Kant. Kant, who is known as a transcendent-rationalist philosophy and founder of criticism, stated the importance of ethical obligations based on the reason for humans. Through his criticism of pure reason (pure reason) and practical reason (practical reason) led to a concept of the highest ethics of happiness, where happiness now can not be achieved without ethics purely based on duty. This is also in line with the teachings of Islam that with a commendable character lead humans to the highest happiness, namely the encounter with God. Islam teaches morals that are based on reason in addition to the main foundation of the Koran and hadith. Then the obligation to do good basically can be recognized by reason without any encouragement from various directions. This article will discuss and show the relevance of ethical obligations and Islamic ethics which are consistent and need not be contested. This research is based on library research using descriptive-analytical and holistic methods. In the end, Western ethical thinking is compatible with Islamic ethics.